Migração e colonização da transamazônica na obra de Odette de Barros Mott - SILVA, José Valtemir Ferreira da (Universidade Federal do Pará, 2020)
The present study aims to reflect on migration process for the colonization of the Transamazon highway in the 1970s from the analysis of the work Transa Amazônica (the great illusion), by the writer Odette de Barros Mott. Thus the approach takes as its starting point the literary work, and the consultation of books, newspapers and other sources of publication of the time, with a view to providing a discussion in order to dialogue on the issues exposed in the narrative. Thus, it is seen that relevant points of immigration and colonization of the Transamazônica were presented, which allow an analysis of the daily life of the highway from the literature. In view of the above, this approach helps to reiterate the importance of the author for national literature, and to collaborate for the various works on the great projects of the Amazon.